Does banknote quality affect counterfeit detection? Experimental evidence from Germany and the Netherlands - Frank van der Horst; Martina Eschelbach; Susann Sieber; Jelle Miedema (Deutsche Bundesbank, 2016)
Counterfeit prevention is a major task for central banks, as it helps to maintain public confidence in the currency. It is often maintained that a high quality of the banknotes in circulation helps the public detect counterfeits. However, there has not been any scientific evidence in support of this assertion so far. The present study is a first attempt to fill this research gap. To investigate whether banknote quality affects counterfeit detection, De Nederlandsche Bank (DNB) and the Deutsche Bundesbank (DBB) conducted a field study in 2014 and 2015 amongst 250 consumers and 261 cashiers in the Netherlands and Germany. Participants received a set of 200 banknotes with either a high or a low average soil level, based on the actual circulation in two different countries. Real-life circulation in both Germany and the Netherlands is in between these values. Each set contained 20 counterfeit notes, which testees were asked to detect. On average, untrained consumers detect 79% of the counterfeits, whereas retail cashiers detect 88%. Cashiers are found to detect more counterfeits when the set is clean, even after controlling for a wide range of personal characteristics in a regression. The estimated effect of cleanliness on the cashiers' detection rate is an additional 0.87 out of 20 counterfeits (4.4%) For consumers, the quality of the sets does not change the hit rate in a statistically significant way.
Keywords: E40; E41; E50; E58; 330; banknotes; counterfeits; banknote quality; signal detection theory